Lived experiences of spiritual emotional intelligence: a Bhagavad Gitā-based indigenous model of psychological wellbeing - Gannamraju, Sai Kiran; Chembrolu, Venkatesh H. (Frontiers in Psychology, 2025)
This study explores the lived experiences of Spiritual Emotional Intelligence (SEI), a psychological framework rooted in the Bhagavad Gitā, a foundational text of Indian spiritual philosophy. Building on a previously proposed model comprising five dimensions—ātma-bodha (self-awareness), samatva (equanimity), niṣkāma-karma (non-attached action), Dharma (virtuous duty), and bhakti (devotion)—we conducted a qualitative study with 26 participants from diverse cultural and professional backgrounds. Semi-structured interviews examined how individuals apply these principles in daily life. Thematic analysis revealed enhanced self-reflection, emotional regulation, intrinsic motivation, ethical decision-making, and a deepened sense of meaning. Even neutral participants resonated with Gitā-based values such as mindfulness, non-attachment, and integrity, demonstrating their universal psychological applicability beyond religious identity. By integrating spiritual and emotional competencies, SEI fosters psychological flourishing and moral purpose. Grounding emotional intelligence in an indigenous Indian worldview, this research expands current understandings of positive psychology and culturally responsive wellbeing. It contributes to indigenous psychology by demonstrating how the Bhagavad Gitā, as a traditional knowledge system, offers a culturally grounded intervention for psychological flourishing in diverse communities, bridging Eastern and global contexts.